Review of Aldo Dinucci. Manual de estoicismo: A visão estóica do mundo. Campinas: Auster, 2023, 144pp., ISBN 978-6587408656 - Falcão, Gabriel Morel (Revista Archai, 2024)
Review of Aldo Dinucci. Manual de estoicismo: A visão estóica do mundo. Campinas: Auster, 2023, 144pp., ISBN 978-6587408656